2021
DOI: 10.1055/s-0041-1731136
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Antimicrobial Susceptibility Pattern of Gram-Positive Pathogens: Three-Year Study at a Tertiary Care Hospital in Mumbai, India

Abstract: Introduction The growing resistance pattern of the gram-positive pathogens along with a steady increase in minimum inhibitory concentration of the currently available antibiotics have led to an increase in morbidity and mortality rates in India. This study aims to access the shifting antibiotic susceptibility paradigm of the gram-positive pathogens in various infections at a tertiary care center. Methods This is a 3-year retrospective observational study which was performed from January 2016 to December 2018 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In support to the above findings, Rajaduraipandi et al also found 31.1% MRSA strains in their investigation, [19]. Various studies from different regions of India including Mumbai, Haryana and Greater Noida, presented the prevalence of MRSA similar to the present study [20][21][22]. More than 50% prevalence of MRSA was observed in MRSA from different states of India.…”
Section: Discussionsupporting
confidence: 89%
“…In support to the above findings, Rajaduraipandi et al also found 31.1% MRSA strains in their investigation, [19]. Various studies from different regions of India including Mumbai, Haryana and Greater Noida, presented the prevalence of MRSA similar to the present study [20][21][22]. More than 50% prevalence of MRSA was observed in MRSA from different states of India.…”
Section: Discussionsupporting
confidence: 89%
“…Then, suspension for inoculation of AST GP 71 card which was used for drug susceptibility test was done by transferring 280μL of culture suspension from the first suspension into another 3mL of sterile saline solution (0.45% to 0.50% NaCl, pH 6.8-7.2) to obtain the final turbidity of 8 × 10 6 CFU/mL. AST-GP71 card which was used for drug susceptibility tests of Gram-positive bacteria contains; penicillin (0.125, 0.25, 1, 2, 8, 64), ciprofloxacin (1,2,4), clindamycin (0.5, 1, 2), daptomycin (0.5, 1, 2, 4, 16), erythromycin (0.25, 0.5, 2), gentamicin (8,16,64), levofloxacin (0.25, 2, 8), linezolid (0.5, 2, 8), minocycline (0.12, 0.5, 2), moxifloxacin (0.25, 2, 8), nitrofurantoin (16,32,64), oxacillin (0.5, 1, 2), quinupristin/dalfopristin (0.25, 0.5, 2), rifampicin (0.25, 0.5, 2), tetracycline (0.5, 1, 2), tigecycline (0.25, 0.5, 1), trimethoprim/sulfamethoxazole (2/38, 8/152, 16/304), and vancomycin (1,2,4,8,16). The concentration values are expressed in µg/mL, which were obtained from the package insert information provided in the kit of AST-GP71 card.…”
Section: Specimen Collection and Processingmentioning
confidence: 99%
“… 1 Due to their quick potential to develop resistance to the currently prescribed medicines, gram-positive bacteria are the main cause of healthcare-associated and community-acquired infections. 2 For both hospital and community-associated infections, Gram-positive bacteria, especially Gram-positive cocci (GPC) such staphylococci, streptococci, and enterococci, are among the most frequent pathogens. 3–6 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations